Transport of Vitamin B(12) in Escherichia coli - Di Girolamo, Paula M. (1971)
The uptake of (60)Co-labeled cyanocobalamin (vitamin B(12)) by cells of Escherichia coli K-12λ was shown to consist of an initial rapid phase (complete in <1 min), followed by a slower secondary phase. Methods enabling the measurement of (60)Co-B(12) uptake after incubation times of 1 to 2 sec were used in studies on the initial rate of B(12) uptake. This initial process showed saturation kinetics, with a V(max) of 56 molecules per sec per cell and a K(m) of 5 nm, and was essentially independent of cellular energy metabolism. No inhibition was obtained with cyanide, fluoride, arsenite, or 2, 4-dinitrophenol, and an energy of activation of 3.8 kcal/mole for this initial phase of uptake was calculated from its response to temperature changes between 15 and 35 C. The inhibition by HgCl(2) (50% at 0.1 mm) but not by 1 mmN-ethylmaleimide or 1 mmp-chloromercuribenzoate was consistent with a role for a relatively inaccessible sulfhydryl residue at the initial B(12) binding site. The secondary phase of B(12) uptake was clearly dependent on the energy metabolism of the cell, and, from its response to temperature, an energy of activation of about 17 kcal/mole was calculated. Cyanide (10 mm), arsenite (10 mm), and 2, 4-dinitrophenol (0.1 mm) gave at least 70% inhibition of the rate of the secondary phase. The formation of other cobalamins, such as 5′-deoxyadenosyl cobalamin, was not an obligate part of B(12) transport. The cells were also able to take up (60)Co-labeled cobinamide cyanide.